2019
DOI: 10.3390/electronics8020163
|View full text |Cite
|
Sign up to set email alerts
|

Application of Artificial Neural Network for Image Noise Level Estimation in the SVD domain

Abstract: The blind additive white Gaussian noise level estimation is an important and a challenging area of digital image processing with numerous applications including image denoising and image segmentation. In this paper, a novel block-based noise level estimation algorithm is proposed. The algorithm relies on the artificial neural network to perform a complex image patch analysis in the singular value decomposition (SVD) domain and to evaluate noise level estimates. The algorithm exhibits the capacity to adjust the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…The generative model is a model that can learn the potential distribution of data and generate new sensor samples. Traditional generative models include the Gaussian model (GM), Bayesian network (BN) [3], S-type reliability network (SRN) [4], Gaussian mixture model (GMM) [5], multinomial mixture model (MMM) [6], hidden Markov model (HMM) [7] and hidden Markov random field (HMRF) [8]. Goodfellow et al [9] proposed generative adversarial networks (GAN) by summarizing the advantages and disadvantages of traditional generative networks.…”
Section: Introductionmentioning
confidence: 99%
“…The generative model is a model that can learn the potential distribution of data and generate new sensor samples. Traditional generative models include the Gaussian model (GM), Bayesian network (BN) [3], S-type reliability network (SRN) [4], Gaussian mixture model (GMM) [5], multinomial mixture model (MMM) [6], hidden Markov model (HMM) [7] and hidden Markov random field (HMRF) [8]. Goodfellow et al [9] proposed generative adversarial networks (GAN) by summarizing the advantages and disadvantages of traditional generative networks.…”
Section: Introductionmentioning
confidence: 99%
“…These prediction methods are mainly classified into three groups: physical propagation models, traditional statistical methods and machine learning methods [13], [14]. Deep learning derives from the study of ANNs, which in many areas of data science have demonstrated a remarkable ability to learn complex, non-linear relationships between sets of variables [15], [16]. The ANN is inspired by the nature of real dynamic systems emulating the human brain, where neurons are layered and interconnected by mathematical functions.…”
Section: Introductionmentioning
confidence: 99%
“…The method was firstly established by Beltrami and Jordan [1] and successively generalized by Autonne [2], Eckart and Young [3]. Since then SVD has successfully been applied on a huge number of different application fields, such as biomedical signal processing [4][5][6][7][8][9][10], image processing [11][12][13][14][15][16][17][18][19], Kalman filtering [20][21][22], array signal processing [23], dynamic networks [24], speech processing [25], simultaneous localization and mapping (SLAM) systems [26], and variable digital filter design [27], to cite just a few.…”
Section: Introductionmentioning
confidence: 99%